فرص وتحديات الاستثمار في الطاقة المتجددة لتعزيز موقع الجزائر في سلاسل الطاقة العالمية والاقليمية-الطاقة الشمسية نموذجا- - لطرش, ذهبية; عرامة, دلال (جامعة الوادي - University of Eloued, 2023)
The research aims to highlight Algeria's position in global and regional energy chains and to study and analyze its potential for renewable energy to take advantage of the opportunities available along the solar energy value chain. The study concluded that despite the availability of the potentials related to the development of solar energy and the opportunities available to bring about an energy transition in Algeria that would allow it to remain one of the main actors in the international (renewable) energy market, the goals of the Energy Transition and Solar Energy Development Program (2015-2030) did not Embodied in light of the accumulation of many financial, technical, legal and organizational obstacles, which calls for the need to expedite their treatment and adopt a real strategy for developing the sector and valuing the competitive advantages available to the Algerian economy in it.
Opportunities and challenges of investing in renewable energy to enhance Algeria's position in global and regional energy chains - solar energy as a model
مقال
Keywords: سلاسل قيمة عالمية ; طاقةمتجددة ; طاقة شمسية ; هيدروجين شمسي ; برنامج صولار 1000; global value chain ; renewable energy ; solar energy ; solar hydrogen , solar program 1000